Impact of Public Health Interventions on the Covid-19 Epidemic: A Stochastic Model Based on Data from an African Island - DC, Nuckchady (Archives of Clinical and Biomedical Research, 2022)
A stochastic model was created to simulate the impact of various healthcare measures on the COVID-19 epidemic. Travel restrictions and point of entry or exit screening help to delay the onset of the outbreak by a few weeks. Population surveillance is critical to detect the start of community transmission early and to avoid a surge in cases. Contact reduction and contact tracing are key interventions that can help to control the outbreak. To promptly curb the number of new cases, countries should diagnose patients using a highly sensitive test.